The Prevalence and Prognostic Role of PD-L1 in Upper Tract Urothelial Carcinoma Patients Underwent Radical Nephroureterectomy: A Systematic Review and Meta-Analysis - Lu, Yi; Kang, Jiaqi; Luo, Zhiwen; Song, Yuxuan; Tian, Jia; Li, Zhongjia; Wang, Xiao; Liu, Li; Yang, Yongjiao; Liu, Xiaoqiang (Frontiers in Oncology, 2020)
Background: Several studies investigating the prognostic role of PD-L1 in upper tract urothelial carcinoma (UTUC) patients after radical nephroureterectomy (RNU) had been published and great controversy existed among them. We, therefore, reported the contemporary prevalence and prognostic value of PD-L1 in UTUC patients who underwent RNU through a systematic review and meta-analysis. Methods: We searched the PubMed, Cochrane Library, EMBASE, and Web of Science by April 1, 2020, to find human studies limited to English language literature reporting the association between PD-L1 expression and clinicopathological features or prognosis in UTUC patients after RNU. We used hazard ratios (HRs) and 95% confidence intervals (CIs), and odds ratios (ORs) and 95% CIs to evaluate the prognostic and clinicopathological values of PD-L1 expression, respectively. We formulated clinical questions and organized following the PICOS strategy. Results: Eight retrospective studies incorporating 1,406 patients were included in the study. The pooled prevalence of PD-L1 in UTUC patients was 21.0% (95% CI = 13.0%-30.0%, I2 = 95.3%). Furthermore, PD-L1 over-expression was related to shorter cancer-specific survival (CSS) in radically resected UTUC patients (HR = 1.63, 95% CI = 1.17-2.26, I2 = 0.0%), but not overall survival (OS) (HR = 1.49, 95% CI = 0.76-2.91, I2 = 74.9%). Subgroup analysis showed significant associations between PD-L1 over-expression and shorter CSS in both Caucasus (HR = 1.72, 95% CI = 1.02-2.92, I2 = 0.0%) and Asian (HR = 1.57, 95% CI = 1.03-2.39, I2 = 23.1%) UTUC patients. Furthermore, PD-L1 was related to invasive depth (pT3+pT4+pT2 vs. pT1+pTa/pTis, OR = 2.53, 95% CI = 1.07-5.96, P = 0.001) and tumor grade of UTUC (High vs. Low, OR = 3.56, 95% CI = 1.82-6.97, P = 0.000). In the cumulative meta-analysis, results indicated the 95%CIs narrowed as the pooled results gradually moved near the null. Conclusions: PD-L1 over-expression was related to worse prognosis and more advanced clinicopathological features in UTUC patients after RNU. It may be useful to incorporate PD-L1 into prognostic tools to select appropriate treatment strategies for UTUC. However, the pooled findings should be considered tentative until ascertained by more researches.